2006
DOI: 10.1021/bi050923c
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Penetrating Peptides pVEC and W2-pVEC Induce Transformation of Gel Phase Domains in Phospholipid Bilayers without Affecting Their Integrity

Abstract: The cell penetrating peptide (CPP) pVEC has been shown to translocate efficiently the plasma membrane of different mammalian cell lines by a receptor-independent mechanism without exhibiting cellular toxicity. This ability renders CPPs of broad interest in cell biology, biotechnology, and drug delivery. To gain insight into the interaction of CPPs with biomembranes, we studied the interaction of pVEC and W2-pVEC, an Ile --> Trp modification of the former, with phase-separated supported phospholipid bilayers (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Indeed, membrane penetration by synthetic 10 as well as by biologically derived 11 molecules/particles is currently under intense investigation. Some biomacromolecules, such as cell-penetrating peptides (CPPs), may be capable of penetrating membranes without overt lipid bilayer disruption/poration [12][13][14][15] . Likewise, synthetic nanomaterials with very small dimensions (molecules, metal nanoclusters 16 , small dendrimers 10 and carbon nanotubes 17 ) can also pass through cell membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, membrane penetration by synthetic 10 as well as by biologically derived 11 molecules/particles is currently under intense investigation. Some biomacromolecules, such as cell-penetrating peptides (CPPs), may be capable of penetrating membranes without overt lipid bilayer disruption/poration [12][13][14][15] . Likewise, synthetic nanomaterials with very small dimensions (molecules, metal nanoclusters 16 , small dendrimers 10 and carbon nanotubes 17 ) can also pass through cell membranes.…”
mentioning
confidence: 99%
“…Previous studies have shown that some cationic nanoparticles and macromolecules penetrate the plasma membrane of cells by generating transient holes 10 ; in contrast, some data suggest that a subset of biological membrane-penetrating macromolecules (for example, CPPs) may be capable of penetrating membranes without causing overt membrane poration [12][13][14][15] . The former mechanism can lead to cell death due to loss of membrane polarization and/or leakage of ions and molecules into/out of the cell.…”
mentioning
confidence: 99%
“…Cationic Au NPs with 50 per cent charge density (relative to hydrophobic ligands) effectively penetrated the lipid membrane without forming holes, whereas significant membrane disruption occurred at higher charge densities [46,57]. Certain cell-penetrating peptides are also known to translocate across membranes without lipid bilayer disruption [107][108][109]. The zwitterionic functionalization of the DPA-QDs used by Wang et al [44] may be responsible for the ability of these NPs to penetrate lipid membranes without compromising bilayer integrity.…”
Section: Passive Mechanisms Of Nanoparticle Uptake By Cellsmentioning
confidence: 99%
“…Likewise, Matile and coworkers have shown that cationic peptides and hydrophobic anions can form neutral complexes that translocate across bilayers [30,31]. Merkle and coworkers have reported that the cationic peptide pVEC (and its derivatives) can induce phospholipid phase transitions, suggesting another mechanism by which PTDs could reach the cytosol [32].…”
Section: Why Is Polyarginine Internalized By Cells?mentioning
confidence: 99%